Progress on Broadband Access to the Internet and Use of Mobile Devices in the United States: Tracking Healthy People 2020 Goals. (January 2017) - Serrano, Katrina J.; Thai, Chan L.; Greenberg, Alexandra J.; Blake, Kelly D.; Moser, Richard P.; Hesse, Bradford W.
Healthy People 2020 (HP2020) aims to improve population health outcomes through several objectives, including health communication and health information technology. We used 7 administrations of the Health Information National Trends Survey to examine HP2020 goals toward access to the Internet through broadband and mobile devices (N = 34 080). We conducted descriptive analyses and obtained predicted marginals, also known as model-adjusted risks, to estimate the association between demographic characteristics and use of mobile devices. The HP2020 target (7.7% of the US population) for accessing the Internet through a cellular network was surpassed in 2014 (59.7%), but the HP2020 target (83.2%) for broadband access fell short (63.8%). Sex and age were associated with accessing the Internet through a cellular network throughout the years (Wald F test, P <.05). The increase in the percentage of people accessing the Internet through mobile devices presents an opportunity for technology-based health interventions that should be explored.